Ochrona prawnokarna dóbr kultury - Sobczak, Jacek (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
Practically since the onset of the Polish state until today, the Polish legislature has been respectably consistent in ensuring a separate framework for the legal and penal protection of cultural assets provided by separate laws to guard them. The regulations which are binding in Poland with respect to the legal and penal protection of historical monuments, both the section pertaining to crimes and that concerning offences, fulfill all the standards stipulated in the regulations of international law. They include an exhaustive range of activities which have the features of crimes and offences against historical monuments.